2014
DOI: 10.21106/ijma.36
|View full text |Cite
|
Sign up to set email alerts
|

Anti-retroviral Therapy and Pregnancy Outcomes in Developing Countries: A Systematic Review

Abstract: Background:Despite significant efforts to understand adverse pregnancy outcome in women receiving Antiretroviral Therapy (ART), ART-related adverse birth outcomes are still poorly understood. We systematically review ART-related adverse birth outcomes among HIV-infected pregnant women; we also review the covariates associated with adverse birth outcomes in the aforementioned group.Methods:The main source for our systematic review was electronic bibliographic databases. Databases such as MEDLINE, PubMed, EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 44 publications
0
23
1
Order By: Relevance
“…By reporting a non-significant burden of PTB with cART, our data are inconsistent with previous findings from other African or Asian settings in newborns, while PTB (15% to 30% in previous studies) was reported to be associated with cART compared to monotherapy used mainly for PMTCT purpose [ 13 , 14 ]. Onsets of PTB appeared more frequent with PI-based regimens [ 15 ], suggesting the need of closer obstetrical monitoring of HIV-infected ANC attendees receiving a second-line ART regimen, since the use of PI is known to favor PTB, especially when initiating cART prior to conception or during pregnancy [ 16 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…By reporting a non-significant burden of PTB with cART, our data are inconsistent with previous findings from other African or Asian settings in newborns, while PTB (15% to 30% in previous studies) was reported to be associated with cART compared to monotherapy used mainly for PMTCT purpose [ 13 , 14 ]. Onsets of PTB appeared more frequent with PI-based regimens [ 15 ], suggesting the need of closer obstetrical monitoring of HIV-infected ANC attendees receiving a second-line ART regimen, since the use of PI is known to favor PTB, especially when initiating cART prior to conception or during pregnancy [ 16 18 ].…”
Section: Discussioncontrasting
confidence: 99%
“…Fekadu et al, found that rate of preterm birth was 10% in women who were started on HAART before pregnancy. 9 In present study, incidence of preterm labor was 16%. Exclusive breastfeeding was practiced among seropositive women with live births in accordance with NACO guidelines.…”
Section: Discussionmentioning
confidence: 43%
“…There have been conflicting data reported on birth outcomes among HIV-positive women who are on lifelong ART compared to HIV negative women. Some studies found that adverse birth outcomes, such as increased preterm deliveries, stillbirths and low birth weight, occurred more frequently among HEI [3][4][5][6][7][8]. Other studies found no association between use of ART and adverse birth outcomes [9,10].…”
Section: Introductionmentioning
confidence: 99%